PENENTUAN TINGKAT TOLERANSI IKAN MAS (Cyprinus carpio L) TERHADAP LIMBAH CAIR INDUSTRI SASIRANGAN - Elrifadah Elrifadah; Arthur Mangalik; Gusti Chairuddin; Bunda Halang (Universitas Lambung Mangkurat, 2011)
Objective of this research were to know the tolerance rate of common carp to liquid waste of sasirangan industries, effect of liquid waste of sasirangan industries to common carp mortality , water quality media, and common carp gills under exposures in 96 hours. Method in this research was Static Bioassay. Tolerance Limit Media (TLM) or Lethal Concentration 50 % (LC50) in 96 hours used to determine of common carp tolerance rate with toxicity test. Before toxicity test, preliminary test be done for determination of upper and lower limit concentration. Completely randomize design with 5 treatments and 3 replicates was used in this research. Application of liquid waste concentration as the treatment was K without liquid waste (0%), A (4,5%), B (5,5%), C (6,5%), and D (7,5%). The data analyzed by using Analysis of Variance (Anova), and Duncan Multiple Range Test (DMRT). Result of the research showed that tolerance rate of common carp to liquid waste (LC50-96 hours) was in concentration 4,9%. Mortality rate was 0%; 33,33% and 76,66% for treatment K, A, and B respectively, but for treatment C and D reaches 100 %. Anova and DMRT result indicated that liquid waste of sasirangan industries had significant effect (P< 0,05) to mortality rate of common carp. Liquid waste also affect water quality media such as temperature, pH, BOD, COD, NH3, Zn, and fenol, all of the parameters increasingly, except DO get decrease. Based of histological analyze, liquid waste had impact to the gills. The higher the liquid waste concentration makes the higher the damage rate.